Terra-i+ - Leverage local knowledge and satellite data to perform high-precision mapping of agroforestry systems - Reymondin, Louis (2023)
Amidst global efforts to combat deforestation, achieve net-zero carbon goals, and comply with rigorous certification standards, agro-industries are facing mounting pressure to substantiate their commitment to sustainable practices. The European Union Deforestation-Free Regulation (EUDR) introduces an extra layer of scrutiny, compelling the adoption of a strategic approach to address environmental concerns. Recognizing the critical role of open science, open data, and open source to enable transparency and trust in traceability systems essential for EUDR compliance, our presentation at the Open-Source Summit in Balibao showcased two pioneering innovations.